2010
DOI: 10.1111/j.1471-4159.2010.06648.x
|View full text |Cite
|
Sign up to set email alerts
|

Human neuroblastoma cells with MYCN amplification are selectively resistant to oxidative stress by transcriptionally up‐regulating glutamate cysteine ligase

Abstract: Neuroblastoma is a sympathetic nervous system tumour whose degree of malignancy, prognosis and therapy resistance has been associated with the amplification of MYCN oncogene. However, the molecular pathway responsible for such resistance is unknown. To contribute addressing this issue, in this study, we have compared the vulnerability of four human neuroblastoma cell lines differentially amplifying MYCN, namely SK-N-BE-2 and IMR-32 (MYCN-amplified cells) and SH-SY5Y and SK-N-SH (MCYN-non-amplified cells), to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In recent literature, it has been reported that human NB cells with MYCN amplification are selectively resistant to oxidative stress by transcriptionally up-regulating glutamate cysteine ligase [31]. These findings could explain, in part, the major vulnerability of MYCN-amplified NB cells following treatment with BSO, an irreversible inhibitor of GSH biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…In recent literature, it has been reported that human NB cells with MYCN amplification are selectively resistant to oxidative stress by transcriptionally up-regulating glutamate cysteine ligase [31]. These findings could explain, in part, the major vulnerability of MYCN-amplified NB cells following treatment with BSO, an irreversible inhibitor of GSH biosynthesis.…”
Section: Discussionmentioning
confidence: 98%
“…We first carried out a dose-response experiment on the effects of ISLQ treatment on cell viability in SK-N-BE(2) cultures. This cell line is MYCN-amplified [36] and therefore a suitable model of aggressive NB, given that MYCN amplification is the main prognostic marker of poor survival in NB [5]. Treatment with ISLQ at concentrations of 5 μM or greater resulted in a dose-dependent decrease (P<0.01) in cell viability in SK-N-BE(2), as measured by MTT assays ( Figure 1A).…”
Section: Effects Of Islq Treatment On Cell Viability In Sk-n-be(2) Cumentioning
confidence: 98%
“…In addition, MYC probably binds to the promoter elements of glutamine transporters, which is associated with enhanced levels of glutamine transporters, e.g., SLC7A5 (solute carrier family 7 member 5, LAT1) and ASCT2 ( Figure 1 ) [ 30 , 31 ]. N-MYC overexpression stimulates mRNA and protein expression of the catalytic subunit of GCL (glutamate-cysteine ligase), and causes rate-limiting step in GSH biosynthesis, which increases GSH level and provides resistance to oxidative damage [ 33 ]. Therefore, targeting MYC can provide a therapeutic window for cancers that have MYC amplification.…”
Section: Glutamine Metabolismmentioning
confidence: 99%